Implementation of Humanistic Value-Based Inclusive Education in Elementary School (Case Study at Al-Azhaar Islamic Elementary School Tulungagung) - Nita Agustina Nurlaila Eka Erfiana; Rita Pusvitasari; Adi Wijayanto (Proceeding International Conference on Islam Law and Society (INCOILS), 2024)
Inclusive education based on humanistic values has the characteristics of implementing child-friendly learning activities, providing comfort and an environment that provides educational needs according to the special needs of persons with disabilities regardless of their shortcomings so that there is equality with humans in general. SD Islam Al Azhaar Tulungagung is one of the inclusive educational institutions that applies humanistic values as a characteristic of learning activities, but in reality there are still various obstacles in its implementation. This studyaims to find inhibiting factors and supporting factors in the implementation of humanistic value-based inclusive education at Al Azhaar Tulungagung Islamic Elementary School and to find solutions to these obstacles so that improvements or efforts can be made to improve the quality of inclusive education. This research method uses a descriptive qualitative approach with miles and huberman analysis techniques. The results of this study found various inhibiting factors and supporting factors in the implementation of humanistic value-based inclusive education at SD Islam Al Azhaar Tulungagung, including those related to quality and management that still needto be improved and better managed. The solutions found in this study are expected to be used as a reference or description of how the management of SD Islam Al Azhaar Tulungagung can make policies in improving the quality of inclusive education at SD Islam Al Azhaar Tulungagung.
Keywords: Education and Character Development; Educational Curriculum and Learning Methods; Pancasila Values in Education